Dose-response effect of incremental lateral-wedge hardness on the lower limb Biomechanics during typical badminton footwork - Yu, L.; Wang, Y.; Fernandez, J. Mei, Q.; Zhao, J.; Yang, F.; Gu, Y. (Journal of Sports Sciences, 2023)
Badminton footwork has been characterised with jump-landing, cross step, side side and lunges, which requires movement agility to facilitate on-court performance. A novel badminton shoe design with systematic increase of lateral wedge hardness (Asker C value of 55, 60, 65, and 70) was developed and investigated in this study, aiming to analyse the dose-response effect of incremental wedge hardness on typical badminton footwork. Stance time and joint stiffness were employed to investigate the footwork performance, and the factorial Statistical non-Parametric Mapping and Principal Component Analysis (PCA) were used to quantify the biomechanical responses over the stance. As reported, shorter contact times (decreased by 8.9%-13.5%) and increased joint stiffness (in side step) of foot-ankle complex were found, suggesting improved footwork stability and agility from increased hardness. Time-varying differences were noted during the initial landing and driving-off phase of cross and side steps and drive-off returning of lunges, suggesting facilitated footwork performance. The reconstructed modes of variations from PCA further deciphered the biomechanical response to the wedge dosage, especially during drive-off, to understand the improved footwork agility and stability.